Leksikon Fauna dalam Peribahasa Jawa Sebagai Representasi Budaya Jawa: Kajian Ekolinguistik - Sutrisno Siswoyo; Mohamad Makincoiri; Agatia Mega Rianda; Fitriana Kartika Sari (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2025)
This research aims to analyze the meaning of Javanese proverbs that contain fauna lexicon elements. This research uses an ecolinguistic approach. This research focuses on expressions in Javanese proverbs that use fauna lexicon. Data were collected by means of qualitative data analysis as three streams of activities that occur simultaneously: (1) data condensation, (2) data display, and (3) conclusion drawing or verification. Data validity was tested with data triangulation by performing the following steps: discussion, double-checking, and expert consultation. The results of the study show that the fauna lexicon has a connection and represents the culture of Javanese society, including related to: (1) negative character, (2) negative nature, (3) positive behavior related to social morals, (4) negative behavior related to human moral behavior, (5) negative behavior related to social life.